PROCEEDINGS OF XV1 CONGRESSO BRASILEIRO DE TRANSPLANTES; XVII CONGRESSO LUSO BRASILEIRO DE TRANSPLANTES; XV ENCONTRO DE ENFERMAGEM EM TRANSPLANTES AND FÓRUM DE HISTOCOMPATIBILIDADE DA ABH. - Associação Brasileira de Transplante de Órgãos, (Brazilian Journal of Transplantation, 2020)
In this issue are presented abstracts of: ETHICS; NURSING AND COORDINATION.